Comparison of methods for the isolation of mycobacteria from water treatment plant sludge - Makovcova, Jitka; Babak, Vladimir; Slany, Michal; Slana, Iva (Antonie van Leeuwenhoek, 2015)
Nontuberculous mycobacteria (NTM) are ubiquitous organisms in all natural ecosystems, including water environments. Several of these species are potential pathogens which affect human health. NTM most commonly cause pulmonary, skin or soft tissue infections. Primary sludge obtained from the water treatment plants of four drinking water reservoirs were subjected to analysis for mycobacteria. Five decontamination methods (5% oxalic acid, modified Petroff, HCl-NaOH, N-acetyl-L-cysteine-sodium hydroxide and 0.05% cetylpyridinium chloride), three growth media (Herrold's egg yolk medium with and without the antibiotic cocktail PANTA and Löwenstein-Jensen medium with sodium pyruvate) and three incubation temperatures (25, 30 and 37 °C) for isolation of mycobacteria were compared in the analysis of 18 sludge samples. To evaluate examined methods, the overall positive, negative, and contamination rate, and these rates in respect to localities are taken into account. Statistical analysis demonstrated that the best combination for the recovery of mycobacteria with the minimum number of contaminating microorganisms is 5% oxalic acid decontamination cultured on Herrold's egg yolk medium with the antibiotic cocktail PANTA at 25 °C. The least suitable is N-acetyl-L-cysteine-sodium hydroxide decontamination cultured on Löwenstein-Jensen medium with sodium pyruvate at 25 °C. From 18 sludge samples we isolated 27 mycobacterial species or groups; Mycobacterium algericum, M. arabiense, M. heraklionense, M. minnesotense, M. moriokaense, M. salmoniphilum and M. vulneris were isolated from the natural water environment for the first time. Because the natural water environment is the main source of potentially pathogenic mycobacteria for humans, it is important to direct particular focus to newly described mycobacterial species.
Keywords: dekontaminace; kultivační média; sladká voda; Mycobacterium; Decontamination; Water Purification; Bacteriological Techniques; odpadní vody; Fresh Water; Sewage; čištění vody; bakteriologické techniky; Culture Media